PERANCANGAN ULANG ALAT PEMBAKARAN IKAN DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Nurulinzany; Tamara (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2024)
The abundant seafood in South Sulawesi, especially Makassar, provides a great opportunity for people to start a food stall business. Traditional cuisine is one of the attractions in the city of Makassar. One of the traditional cuisines that is in great demand is grilled fish, both for immigrants and people who live in Makassar. The purpose of this study is to design a fish grilling tool with the Quality Function Deployment (QFD) approach. The QFD method is a method in designing products/services based on consumer needs. The results of identifying consumer needs are used to compile a quality house or House of Quality (HOQ). Based on HOQ, the highest weights are the size of the fish grilling tool (17.7%), the charcoal container (17.6%), and the rectangular design (15%). So the design carried out by the researcher is a fish grilling tool that has automatic charcoal disposal and a fan measuring 100x40x90cm and a fish grilling tool that can be folded so that it is easy to carry and move.